Single-cell RNA-seq reveals TOX as a key regulator of CD8+ T cell persistence in chronic infection - Yao, Chen; Sun, Hong-Wei; Lacey, Neal E.; Ji, Yun; Moseman, E. Ashley; Shih, Han-Yu; Heuston, Elisabeth F.; Kirby, Martha; Anderson, Stacie; Cheng, Jun; Khan, Omar; Handon, Robin; et al. (Nature Immunology, 2019)
Progenitor-like CD8+ T cells mediate long-term immunity to chronic infection and cancer and respond potently to immune checkpoint blockade. These cells share transcriptional regulators with memory precursor cells, including T cell-specific transcription factor 1 (TCF1), but it is unclear whether they adopt distinct programs to adapt to the immunosuppressive environment. By comparing the single-cell transcriptomes and epigenetic profiles of CD8+ T cells responding to acute and chronic viral infections, we found that progenitor-like CD8+ T cells became distinct from memory precursor cells before the peak of the T cell response. We discovered a coexpression gene module containing Tox that exhibited higher transcriptional activity associated with more abundant active histone marks in progenitor-like cells than memory precursor cells. Moreover, thymocyte selection-associated high mobility group box protein TOX (TOX) promoted the persistence of antiviral CD8+ T cells and was required for the programming of progenitor-like CD8+ T cells. Thus, long-term CD8+ T cell immunity to chronic viral infection requires unique transcriptional and epigenetic programs associated with the transcription factor TOX.
CRIS-Team Scopus Importer:2023-03-23